2016
DOI: 10.1111/1753-6405.12548
|View full text |Cite
|
Sign up to set email alerts
|

No official identity: a data linkage study of birth registration of Aboriginal children in Western Australia

Abstract: Objective: Evidence of identity, particularly a birth certificate, is essential to access many rights. However, the births of many Aboriginal Australians are not registered when they are infants. We examined factors related to birth registration among Western Australian children born to Aboriginal mothers. Methods:All births to Aboriginal mothers in the Midwives Notification System in Western Australia (WA) from 1980 to 2010 were linked to birth registrations. Associations between registration and maternal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…This led to certain differences between the perinatal data and our study cohort (Table 1). Similar differences have been reported in other studies linking the state birth registrations and perinatal data collections in WA (for Indigenous births only), NSW and Queensland [22,23,24] and should be kept in mind when generalising the data to all births. However, the study is representative of all registered births and includes a large cohort involving 97.5% of all live births (89.8% of all Indigenous births) in the NSW and WA perinatal data collection.…”
Section: Discussionsupporting
confidence: 81%
“…This led to certain differences between the perinatal data and our study cohort (Table 1). Similar differences have been reported in other studies linking the state birth registrations and perinatal data collections in WA (for Indigenous births only), NSW and Queensland [22,23,24] and should be kept in mind when generalising the data to all births. However, the study is representative of all registered births and includes a large cohort involving 97.5% of all live births (89.8% of all Indigenous births) in the NSW and WA perinatal data collection.…”
Section: Discussionsupporting
confidence: 81%
“…Due to their young age at death, most infants have had limited contact with health and other administrative systems and lack the opportunity to have their Indigenous status captured in multiple presentations across a range of datasets. Consequently, studies of infant health outcomes rely heavily on birth registration and perinatal data collections 29,31,34 . A low rate of linkage of birth and death registration in the SUDI data was observed (77.6%; with only 3.1% explained by infants born outside Queensland), although the reasons for this are unclear.…”
Section: Discussionmentioning
confidence: 97%
“…It may relate to operational processes since this data (obtained from the Child Death Register) was linked by the Registry of Births Deaths and Marriages, which does not have a dedicated data linkage and statistical analysis team. Compounding this issue, Indigenous births are registered at a significantly lower rate than non‐Indigenous births 24,31,34 . A recent Queensland investigation found that 15–18% of births to Aboriginal mothers were not registered compared with an under‐registration rate of 1.8% for births to non‐Aboriginal mothers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the death registrations, the SIQ is used on the birth registration documents, however, there are known barriers to ensuring that births are registered, particularly for those who live remotely, including costs or perceived costs, a lack of online infrastructure and limitations in culturally appropriate services [60]. Reports from Queensland and Western Australia utilising data linkage to assess completeness of birth registrations describe that 17 percent and 18 percent, respectively, of Indigenous babies were not registered at birth [61,62]. While there has been some work undertaken to describe the extent of the under-registration of births in Australia, there is yet to be a comprehensive assessment of the impact that under-registrations and under-enumeration of Indigenous births can have on indicators, specifically infant and child mortality rates.…”
Section: Censusmentioning
confidence: 99%